Polimorfismos no gene da adiponectina como biomarcadores de transtorno neurocognitivo em idosos - Quirino, Karoliny Gomes (2021)
Adiponectin (ADPN), expressed by the ADIPOQ gene, is one of the most abundant adipokines in the body, being a protein hormone that modulates several metabolic processes, including the regulation of blood glucose. It has antiinflammatory and antioxidant function. It acts in insulin sensitization, being one of the protective factors for some diseases such as obesity, diabetes and metabolic syndrome, in which inflammation is one of the central events. Recent evidence suggests that low plasma levels of ADPN can lead to the development of Neurocognitive Disorder (TNC) and dementia, its severe form, through neuroinflammation, obesity and or insulin resistance. Its recently discovered action on neural zones suggests potential benefits for memory and synaptic plasticity.Thus, the hypothesis is that the SNPs in the ADIPOQ gene are associated with the development of TNC and in its most severe form, dementia, and therefore, are good genetic biomarkers of TNC risk. In this context, the objective of this work was to verify whether the polymorphisms are associated with TNC / dementia, anthropometric, biochemical and clinical parameters.1118 participants in the SABE study (Health, Well-Being and Aging) were selected, with complete data on age, sex, biochemical tests, anthropometry, type 2 diabetes, stroke and Mini Mental State Examination (MMSE). Patients who scored below the cut-off line (13) of the MMSE were considered to have TNC (N = 144) and of these, those who scored above the cutoff point (5) in the Pffefer Questionnaire for Activities were considered Functional (N = 111) and below considered as having Light TNC (N = 33). SNPs rs17300539 (11391G> A); rs 266729 (11377C> G); rs 2241766 (45T> G) and rs 1501299 (276G> T) of the ADIPOQ gene were evaluated in an association study. Of the total number of participants, 12.9% (N = 144 patients) had TNC, being 111 with Major TNC or Dementia (111/1118 - 10%) and 33 with Light TNC (33/1118 - 3%). SNPs 11377C >G (rs266729 P = 0.021) and 276G> T (rs1501299 P = 0.016) are associated with the TNC when considering age. Stronger associations were related to increasing age through obesity for SNPs 11377C> G (rs266729; P = 0.005), 113910G> A (rs17300539; P = 0.045) and 276G> T (rs1501299 P = 0.030). Other associations have been identified. We conclude that the development of TNC is associated with SNP in the ADIPOQ gene and that TNC has a genetic architecture related not only to aging, but also to metabolism.